4-(3-Chlorophenyl)-3-[(2,6-difluorobenzyl)sulfanyl]-5-(3,4,5-trimethoxyphenyl)-4H-1,2,4-triazole - Hoong-Kun Fun; Safra Izuani Jama Asik; B. Chandrakantha; Arun M. Isloor; Prakash Shetty (Acta Crystallographica Section E, 2011)
In the title compound, C24H20ClF2N3O3S, the essentially planar triazole ring (r.m.s. deviation = 0.001 Å) forms dihedral angles of 22.35 (10), 68.17 (10) and 42.01 (10)° with the mean planes of the trimethoxyphenyl, chlorophenyl and difluorophenyl rings, respectively. A weak intramolecular C—H...π interaction occurs. In the crystal, molecules are linked into sheets lying parallel to the bc plane by C—H...O and C—H...N hydrogen bonds. The crystal packing also features weak C—H...π interactions.